Persepsi Konsumen Muslim terhadap Sertifikasi Halal pada De Dapoer Rhadana Hotel Kuta Bali - Nur Dwi Astutik; Ahmad Ahsin Kusuma Mawardi; Agus Mahardiyanto (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
De Dapoer-Rhadana Hotel Kuta Bali is one of the restaurants that has been certified halal in its products. As consumers especially muslim consumers should be more vigilants, selective and observant in choosing restaurants while in Bali that are halal to eat and thayyib. The method used is this study is qualitative descriptive that aims to know the muslim consumer’s perception of halal certification of De Dapoer - Rhadana Hotel Kuta Bali. The results of this study showed that the muslim consumer perception of halal certification in De Dapoer - Rhadana Hotel Kuta Bali assumer or perception that halal certification is important. Because the respondents know that to guarantee the halalness of product by means of halal certification labels. The final results of the study showed that consumers consider halal certification is important.